2011
DOI: 10.3109/14767058.2011.607567
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of nosocomial infections and surveillance of emerging resistances in NICU

Abstract: Neonates hospitalized in NICU are at risk for healthcare associated infections because of their poor immune defenses, related to gestational age, colonization of mucous membranes and skin with nosocomial microorganisms, exposure to antibiotics, invasive procedures and frequent contacts with healthcare workers (HCWs). Healthcare associated infections are the major source of morbidity and mortality in NICU in the developed world. Most infections are caused by Gram-positive organisms, fulminant sepsis are often a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 13 publications
0
38
0
3
Order By: Relevance
“…Time-series analysis in conjunction with a broadly applied a stewardship program. 12,16 appears to be a powerful clinical tool for the analysis and prediction of infectious diseases and has potential to help reduce the incidence of HAIs and HA-MRSA infections.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Time-series analysis in conjunction with a broadly applied a stewardship program. 12,16 appears to be a powerful clinical tool for the analysis and prediction of infectious diseases and has potential to help reduce the incidence of HAIs and HA-MRSA infections.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has identified numerous risk factors for HA-MRSA, including prolonged hospital stay, exposure to broadspectrum antibiotics and exposure to a greater number of antimicrobials. 11,12 Lucet et al 13 reported that the factors associated with MRSA in the ICU were older than 60 years, prolonged hospital stay, history of hospitalization or surgery and presence of open skin lesions in directly admitted patients. Antimicrobial use and infection control measures have important roles in the prevention of HAIs, 14 but the need for a policy of active surveillance is controversial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early feeding with human milk has been considered to be an important prevention strategy for nosocomial infections in NICUs [24]. A study on beta-lactam-resistant aerobic commensal fecal flora of newborns showed that feeding with tube feed was protective during the hospital stay and that failure to feed with breast milk was a risk factor for colonization with extended-spectrum beta-lactamaseproducing bacteria after discharge [25].…”
Section: Discussionmentioning
confidence: 99%